ChemInform Abstract: A General Method for Aminoquinoline‐Directed, Copper‐Catalyzed sp2 C—H Bond Amination. Issue 36 (August 2016) - Roane, James; Daugulis, Olafs
Abstract: Primary, secondary, and aromatic amines, heterocycles as well as electron‐deficient aromatic and heteroaromatic are employed as amine coupling partners using Cu(OAc)2 or CuCO3 ·Cu(OH)2 as catalysts and oxygen from the air as the terminal oxidant.